A study in language contact - Makoe, Bridgitte Pinky (Department of English Language and Literature, 2016)
The objective of this thesis is to report on a research project investigating the language behaviour of Sotho-English bilingual students at the University of Cape Town (hereafter UCT). Sotho is used here as an umbrella term to refer to the Sotho group of languages; Sesotho (Southern Sotho), Sepedi (Northern Sotho) and Setswana. UCT is a multilingual institution in the sense that the students, and to some extent the lecturers, are proficient in a number of languages including English, Afrikaans, and a wide range of African languages from within and outside South Africa. At the time of the study in 1997 UCT was multiracial with a majority of white students and a minority of African students. At a general level the concept of language contact is the superordinate linguistic and philosophical category underpinning the thesis. At a more specific level, the thesis examines three related concepts; code-switching, code-mixing and borrowing. It is based on theoretically and empirically founded distinctions between code-switching, code-mixing and borrowing. Empirically the data was collected surreptitiously. The ethical questions about who researches what and whom are acknowledged. Permission to use the covertly collected data was sought after the recording from all informants and was granted. The data from the covert recordings was triangulated with interviews with the informants. Theoretically the thesis uses a number of approaches to describe and explain language contact: structuralist, interactionist and psycho-social approaches although the dominant framework is a structuralist one. Sociologically the thesis demonstrates that code-switching constitutes a variety in which speakers exhibit differing degrees of skilled abilities and may be unmarked or marked depending on the extent which it reinforces or violates community norms. The linguistic varieties must be understood in terms of individual repertoires and community speech economies. Code-switching may represent a normal, routine way of use or could be said to violate the expectations of how one should behave. Bibliography: pages 102-109